Pengaruh Cekaman Kekeringan terhadap Pertumbuhan dan Kadar Flavonoid Total Tumbuhan Tabat Barito (Ficus deltoidea Jack) - Manurung, Hetty; Kustiawan, Wawan; Wijaya Kusuma, Irawan; Marjenah (Jurnal Hortikultura Indonesia, 2019)
This research aimed to evaluate the effects of drought stress on growth and the total flavonoid content of tabat barito plant (Ficus deltoidea Jack). The experiment was conducted in the greenhouse Faculty of Mathematics and Natural Sciences, Mulawarman University, using a completely randomized design consisted of 4 levels drought stress including 100%, 80%, 60%, and 40% field capacity. The F. deltoidea maintained for 9 months old and investigated for the growth parameter (plant height, leaf number, leaf area, the number of branches, stem diameter, and biomass), phytochemical screening, and the total flavonoid content. Drought stress has a significant effect on plant height, the number of branches, stem diameter and biomass. Based on the phytochemical screening, leaf extract of F. deltoidea contained alkaloids, phenolics, flavonoids, steroids, and coumarins. The highest total flavonoid content observed under 40% field capacity (430.77 μg CE mg-1 extract) and the lowest total flavonoid content observed under 100% field capacity (282.05 μg CE mg-1 extract). In general, this results showed that the drought stress motivated a significantly decreased of growth and significantly increased of total flavonoid content of leaves extract. Keywords: cultivation, drought stress, flavonoid, tabat barito (Ficus deltoidea)